Major features of Japan FDI to Vietnam for recent years - Vu, Van Ha (Vietnam National University, Hanoi, 2020)
Thirdly, the overall effectiveness of investment projects has improved. This is obvious in a higher rate of execution of investment capital, a low number of cancelled investment licences, an increase of product export and increasing employment opportunities. This paper suggests some solutions in order to improve investment envirionment in future